Bancassurance як цінний інструмент розвитку фінансового ринку - Садура, О. Б.; Агрес, О. Г.; Sadura, O.; Agres, O. (Видавництво Львівської політехніки, 2020)
Обґрунтовано поняття “bancassurance” як процес взаємодії банків і страхових компаній. Досліджено позитивні та негативні стороні від цієї кооперації – продаж страхових полісів разом із продуктами, пропонованими банками. Розглянуто різні тлумачення bancassurance в сучасних умовах. Виділено переваги та недоліки банко-страхування для обох суб’єктів цієї діяльності. Виявлено важливий чинник щодо утворення банківсько-страхового співробітництва – нові канали дистрибуції страхових компаній. Проаналізовано стан ринку bancassurance у розвинутих країнах Європи. Визначено специфіку розвитку bancassurance в Україні. Перелічено компанії-лідери на українському ринку банкострахування. Вказано доцільність створення фінансового супермаркету. Запропоновано напрями подальшого розвитку bancassurance в Україні.

The relevance and objectives of the work are the need to expand and improve the interaction of financial intermediaries, to improve the quality and increase the volume of financial services provided. The object of research is the integration of banks and insurance companies for the distribution of insurance products through the banking network both in Ukraine and abroad. It should be noted that for Ukraine it would serve as a new step in the development of the economy as the interaction of two capitals, may become a promising collaboration that will lead to financial sustainability in these sectors in Ukraine. The main goal of our study is to identify new prospects and having the use of bancassurance in the modern financial market. The concept of “bancassurance” as a process of interaction between banks and insurance companies. We investigated the effect of this cooperation is the sale of insurance with products offered by banks. Considered different interpretations of bancassurance in the modern world. The advantages and disadvantages of Bank assurance to both parties of such activities. It is proved that the purpose of the functioning of banks and insurance companies is profit. Revealed an important factor in creating banking-insurance cooperation – new distribution channels of insurance companies. Analyzes the market of bancassurance in the developed countries of Europe. Shows a deep global integration of insurance companies into the banking sector, and also the fact that, in contrast to the Ukrainian, foreign banks are a significant part of the profits from the sale of insurance products. Graphically shows the distribution of insurance products through banking institutions in Europe. Determined the specifics of the development of bancassurance in Ukraine. In the course of the research, it was determined that the highest form of integration of education is a financial supermarket – the most common and effective strategy implementation, the Bank assurance that is inherent in the world’s market leaders in financial services. We believe that at this stage of development of the domestic financial market application of the model “Аgreement on cooperation in the dissemination” would bring Ukraine positive results. However, at the initial stage of the formation of such a supermarket would be an important election and a clear definition of its objectives. First of all, you can identify at least 4 areas for which a financial intermediary in the context of modernity to define the purpose, relying on our expectations. So, this includes income, interaction with potential clients, the requirements and welfare of employees and directly to social responsibility. Applying this method of cooperation, the primary goal of forming such a supermarket will be to increase the income of each participant through synergistic effect and minimize costs, expand the boundaries of the segment of work, strengthen the image and reputation of the partner companies. The companies-leaders in the Ukrainian bank insurance market are listed. The reasons for the underdevelopment of bancassurance in Ukraine include low solvency and distrust of the country’s population in the banking sector; the global financial and economic crisis, which significantly affects the overall economic situation in Ukraine; excessive credit risks of the bank; excessive requirements for accreditation of insurers by banking institutions. The dominant trends in the development of bancassurance in Ukraine should be increasing customer confidence; improving the legislative framework; increasing the competitiveness of both banks and insurance companies; mandatory information for potential customers.
Bancassurance as a valuable financial market development instrument
Keywords: bancassurance; фінансовий супермаркет; інтеграція; банк; страхова компанія; financial supermarket; integration; bank; insurance company; G; 220; 336.71